Zinc-Phthalocyanine-Loaded Extracellular Vesicles Increase Efficacy and Selectivity of Photodynamic Therapy in Co-Culture and Preclinical Models of Colon Cancer - Pablo Lara; Ruben V. Huis in 't Veld; Carla Jorquera-Cordero; Alan B. Chan; Ferry Ossendorp; Luis J. Cruz (MDPI AG, 2021)
Photodynamic therapy (PDT) is a promising and clinically approved method for the treatment of cancer. However, the efficacy of PDT is often limited by the poor selectivity and distribution of the photosensitizers (PS) toward the malignant tumors, resulting in prolonged periods of skin photosensitivity. In this work, we present a simple and straightforward strategy to increase the tumor distribution, selectivity, and efficacy of lipophilic PS zinc phthalocyanine (ZnPc) in colon cancer by their stabilization in purified, naturally secreted extracellular vesicles (EVs). The PS ZnPc was incorporated in EVs (EV-ZnPc) by a direct incubation strategy that did not affect size distribution or surface charge. By using co-culture models simulating a tumor microenvironment, we determined the preferential uptake of EV-ZnPc toward colon cancer cells when compared with macrophages and dendritic cells. We observed that PDT promoted total tumor cell death in normal and immune cells, but showed selectivity against cancer cells in co-culture models. In vivo assays showed that after a single intravenous or intratumoral injection, EV-ZnPc were able to target the tumor cells and strongly reduce tumor growth over 15 days. These data expose opportunities to enhance the potential and efficacy of PDT using simple non-synthetic strategies that might facilitate translation into clinical practice.